Can Public Discussion Enhance Program Ownership? - Isard, Peter (IMF Working Papers; Working Paper ;, 2004)
We use the concepts of deliberative democracy from political science and cheap talk from economics to develop a better understanding of how public discussion can contribute to building and demonstrating ownership of IMF programs and hence to program success. We argue that ownership is more complex than many discussions of it would suggest, since it must include not only the willingness to carry out a program, but also the technical capacity and especially the political ability to do so. Public discussion can serve a number of purposes, each of which can be better understood by moving to a more formal treatment. We illustrate our points by means of simple examples. We also consider some of the drawbacks of public discussion, especially as applied to IMF programs.